A review of the genus Tabanus Linnaeus, 1758 (Diptera: Tabanidae) from Egypt - El-Hassan, Gawhara M.m. Abu; Badrawy, Haitham B.m.; Fadl, Hassan H.; Mohammad, Salwa K. (Zootaxa, 2013)
The Egyptian fauna of the genus Tabanus Linnaeus is reviewed. Only seventeen species are recognized instead of the previous 21. This is because six species have been removed as doubtful records, and an additional two species have been added (T. leucostomus Loew, 1858 (new record) and T. arenivagus Austen, 1920). A key to Egyptian species of Tabanus is included together with illustrations. Specimens examined and distributions are given for each species. The status of the six species doubtful to occur in Egypt is discussed.